Mapping the landscape of serious digital language learning games: Towards a Serious-Digital Game-based Language Learning (S-DGBLL) teacher competence framework - Pitura, Joanna; Turula, Anna; Nowak, Sabina; Jakubik, Joanna; Asotska-Wierzba, Yuliya (Neofilolog, 2024)
Serious games have been gaining increasing attention in the field of digital game-based language learning (DGBLL). However, to incorporate serious games into foreign/second language (L2) classrooms, teachers must be prepared with requisite knowledge and skills. To this end, following PRISMA guidelines, this study conducted a systematic review of research on serious digital language learning games with two aims. The main objective of this study was to map out the issues pertaining to serious digital language learning games that are currently being addressed in empirical studies in the DGBLL area. The secondary objective was to leverage the findings to inform the development of a research-based framework of expertise for L2 teachers intending to incorporate serious digital game-based language learning (S-DGBLL) in their classrooms. Fifty articles published until April 2023 were analysed in terms of research methodologies, pedagogical characteristics, game design, and outcomes. The findings have implications for the proposal of an S-DGBLL teacher competence framework.